Eco-genetic analysis of the inheritance of fiber yield in cotton hybrids with various crossing methods - Sysa, Aliaksei; Boboyev, Sayfulla; Mirakhmedov, Mirvakhob; Abdrakhmanov, Tokhtasin; Amanturdiev Икром (Journal of the Belarusian State University. Ecology, 2024)
Improving the quality of cotton fiber is one of the most important tasks of the breeding programs of states involved in cotton growing. One of the pressing problems is the creation of new varieties and hybrids of cotton with high productivity, resistance to pests and diseases, adaptability to extreme environmental conditions and global climate change. The purpose of the study is to establish the nature of inheritance and variability in the yield and fiber length of cotton hybrids from various ecological and geographical zones, obtained using methods of interline and interspecific complex hybridization. As a result of the research, it was revealed that for the studied crossing combinations involving lines L-501 and L-525 with a whole leaf form in F2 with whole leaves, the f i ber yield is greater than in plants with three-lobed and f i ve-lobed leaf forms, which indicates a dominant homozygous state Inl gene (whole leaf form). For the crossing combinations L-653×L-681, L-650×L-681, it was shown that the lntn gene (mutant type of «pakhtaabad» bush) does not have a significant effect on the expression of genes that determine fiber yield. In interspecific complex hybrids F1-F4, the appearance in early generations of recombinants with positive indicators located in the right classes of the variation series was discovered, which shows the possibility of improving the trait and identifying families with high fiber yield starting from F4, by undefined selection among these recombinants. The resulting complex interspecific cotton hybrids have a new combination of economically valuable traits and ecological plasticity, which will allow them to be cultivated in the unfavorable ecological and geographical conditions of the deserts of Uzbekistan.